Preparation and characterisation of cattle bone based hydroxyapatite implant coatings using electrostatic spray deposition - Muhammadsarn Ii Baru (2018)
The biocompatibility of orthopaedic or dental metallic implants can be significantly enhanced by the coatings of bioceramic materials. Currently, various deposition techniques such as plasma spraying, magnetron sputtering and pulsed laser deposition can be used for the metallic implant coating. Nevertheless, these methods are addressed as a high temperature processing and manufacturing cost. Electrostatic spray deposition (ESD) has gained interest due to its simple and economical process involving a room temperature processing. Hence, the objectives of this study have focused on preparation and characterisation of cattle bone based hydroxyapatite (cHA) stainless steel implant coatings using ESD. Process parameters including electrode-substrate distance, applied electrical voltage, powder feed rate and current were optimised. The chemical composition of cattle bone powder was investigated both before and after coating by X-ray diffractometry (XRD). The XRD pattern of cattle bone powder demonstrated that all significant peaks matched with HA both before and after coatings. The morphological characteristic of the coatings was examined by scanning electron microscope (SEM). The surface morphology of the coatings showed a homogeneous and dense layer. The average thickness was about 40 μm. The IN VITRO bioactivity of cHA coatings was investigated by an acellular simulated body fluid soaking experiment. The accelerated apatite precipitation process occurred on the cHA-coated stainless steel surfaces compared to the uncoated stainless steel surfaces. Thus, the use of ESD is a promising technique in producing cHA coatings for biomedical applications. © (2013) Trans Tech Publications.